Implementasi Pemberian Bantuan Hukum Di Kota Samarinda Berdasarkan Perspektif Administratif Dalam Undang-Undang Nomor 16 Tahun 2011 - Abdul Mukmin Rehas, S.H., M.H (Law Department, University of Widya Gama Mahakam Samarinda, 2015)
ABSTRACT Legal aid is a very important means in terms of gaining the needs of the poor society in this case to obtain the justice and retain their rights because not all people are able to afford to pay the attorneys' fees that are reliable and professional to retain the rights and ensure legal certainty nor justice for one of the parties. Thus the government needs to provide legal assistance to the community with low level economy to find the justice for him, and mandatory for the government to implement the City Legal Assistance in Samarinda in order to run in perspective and in accordance with law No. 16 in 2011.